The role of calcium and nitrite in triple negative breast cancer - Alkuraythi, Dalal (Journal of medical and pharmaceutical sciences, 2017)
In 2017, approximately 252,000 of American women were diagnosed with breast cancer of which 25% of these cases were classified as estrogen receptor-negative (ER-). A substantial subset of these breast tumors do not express estrogen or progesterone receptors nor do they overexpress HER2 and have been therefore designated as triple negative breast cancers (TNBC). TNBC has been shown to be more aggressive and have poor prognosis. Androgen receptor (AR) is expressed in 70% of ER- breast cancer. Even though, the ER role in breast cancer is well known and recognized, little is known about the clinical importance of androgens and AR in breast carcinogenesis. Ligand bound AR translocates to the nucleus, and then a cascade of events occurs culminating with transcription of target genes. Aim: Hypothesizing that activation of androgen receptor (AR) by calcium or nitrite results in increased proliferation in AR+ TNBC, hence creating an opportunity to be able to attack triple negative breast cancer cells via the androgen receptor and thereby be able to shrink the cancerous cells. Methods: Estrogen receptor negative, androgen receptor positive MDA-MB 453 breast cancer cells were treated with synthetic androgen (R1881); non-steroidal anti-androgens casodex, flutamide, or hydroxyl flutamide; calcium channel blockers mibefradil (T type) and methoxyverapamil (L type); or nitric oxide synthase inhibitor nitroarginine (LNNA) for 96h. Results: Cells treated with calcium showed a higher proliferation rate in comparison to control cells. In contrast cells treated with methoxyverapamil or mibefradil at higher concentrations, showed decreased cell growth. Conclusion: Data suggest that the overexpression of calcium channels and nitric oxide synthase, one or both of them, is a major contributor in activating androgen receptor leading to cell growth and survival of androgen receptor-positive breast cancer, and hence androgen activation in triple negative breast cancer. The data also suggest that FDA approved calcium channel blockers and NOS inhibitors maybe useful for the treatment of AR+ TNBC.